Protection against indirect expropriation: The road to clarification in modern investment treaties - Salcedo Machado, José Germán (2025)
In this article, the author reviews the efforts undertaken for decades by investment doctrine and tribunals to interpret when an indirect expropriation occurs, and discusses the current trend towards textual clarification of this protection in modern investment protection treaties.